Swimming overuse injuries - Jones, J. H. (Physical Medicine & Rehabilitation Clinics of North America, 1999)
Swimming injuries are unique in that they involve upper limb overuse more than lower limbs and that swimming is performed in a non-weight-bearing fluid setting. Identifying the mechanism of injury and prescribing appropriate management is not easy unless one has a thorough understanding of proper technique of the four competitive strokes. Understanding the psychology of swimming athletes will improve outcome and compliance. The goals of this article are to familiarize the reader with the diagnosis and management of swimming injuries and to improve the physician's effectiveness in dealing with swimmers through a thorough understanding of technique and psychology.